Federal calorie labelling compliance at US chain restaurants. (21st January 2020) - Cleveland, Lauren P.; Simon, Denise; Block, Jason P.
Summary: Objective: The 2010 Affordable Care Act included a provision requiring chain food establishments to post calories on menus. In 2017, prior to the final implementation of the law, 59 of 90 top‐selling chains had fully implemented labelling. This study extends the documentation of compliance to the 200 top‐selling chains after the nationwide requirement went into effect in May 2018. Methods: To determine if restaurants were compliant with the federal menu labelling law, objective information was collected from all 197 of the 200 highest grossing restaurant chains in the United States. The study team obtained information via site visits and internet searches for a convenience sample of restaurants within each of these chains. Results: 94% had implemented menu calorie labelling after the May 2018 deadline. Of the 11 chains not complying, six were full‐service restaurants. Conclusion: Most chain restaurants have complied with the federal calorie labelling law, suggesting that compliance is attainable for all chains. Given this finding, the Food and Drug Administration should initiate enforcement of labelling for noncompliant chains.